Persahabatan Penjajah dan Bangsa Jajahan di Hindia Belanda: C. Snouck Hurgronje dan Haji Hasan Mustapa - JAJANG A ROHMANA (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2016)
This study aims to analyze the friendship between the colonizer with the colony in the Dutch East Indies. The study focuses on a number of works and letters of Haji Hasan Mustapa to C. Snouck Hurgronje. Mustapa was the Hoofd penghulu (Chief-penghulu) of Aceh and Bandung. He is a close friend of Snouck since his first met in Mecca in 1885. Through the social-intellectual history approach, the study tries to explain their closeness which are no longer merely a relationship between employer and employee, but has penetrated deeply into the true brother- hood and kinship ties. Snouck who representated as a colonial master looked Mustapa as a figure who has unique talent and character which achieve high knowledge about Islamic law and Sundanese customs. Instead, Mustapa looked Snouck as his close friends who have a commitment to defend each other. Mustapa shed his impression and expectation to meet him again someday in his letters. Mustapa often shed tears when remembering the time of togetherness that will not be forgotten throughout his life. It is an interplay friendship that have never imagined in shaping the face of colonialism in Indonesia, which its influence cannot be ignored until now.